A sense of self : memory, the brain, and who we are - O'Keane, Veronica (W.W. Norton & Company, 2021)
"How do our brains store-and then conjure up-past experiences to make us who we are? A twinge of sadness, a rush of love, a knot of loss, a whiff of regret. Memories have the power to move us, often when we least expect it, a sign of the complex neural process that continues in the background of our everyday lives. This process shapes us: filtering the world around us, informing our behavior and feeding our imagination. Psychiatrist Veronica O'Keane has spent many years observing how memory and experience are interwoven. In this rich, fascinating exploration, she asks, among other things: Why can memories feel so real? How are our sensations and perceptions connected with them? Why is place so important in memory? Are there such things as "true" and "false" memories? And, above all, what happens when the process of memory is disrupted by mental illness? O'Keane uses the broken memories of psychosis to illuminate the integrated human brain, offering a new way of thinking about our own personal experiences. Drawing on poignant accounts that include her own experiences, as well as what we can learn from insights in literature and fairytales and the latest neuroscientific research, O'Keane reframes our understanding of the extraordinary puzzle that is the human brain and how it changes during its growth from birth to adolescence and old age. By elucidating this process, she exposes the way that the formation of memory in the brain is vital to the creation of our sense of self"--